OUTERMODEL DETERMNAN VALUE OF THE FIRM GO PUBLIC GENERAL BANKING SECTOR IN INDONESIA STOCK EXCHANGE - Manafe, Henny Angri (Archives of Business Research, 2019)
The value of the company shows the value of assets owned by the company such as securities. If the company’s stock price increases, the value of the company will also increase, which in the end will increase shareholders’ prosperity. Gitman (2006: 352) said that "Company Value is the real value per share of the company that will be obtained if the company’s assets will be sold according to the stock price". This study aims to find out the model determinant indicator of the value of the firm of the general banking sector listed on the Indonesia Stock Exchange in 2015-2017. The population in this study were 33 general banking companies. The sampling technique used a purposive sampling method and obtained 16 general banking companies as samples. The data analysis technique used is PLS SEM. Based on the results of the outermodel analysis, it is known that the most dominant influence on the value of the firm is an indicator of credit risk, namely Debt Equity Ratio (DER), Good corporate governance, credit portfolio, income growth, macroeconomics, earnings and capital which are proven as indicators of value of the firm